2012
DOI: 10.1371/journal.pone.0029719
|View full text |Cite
|
Sign up to set email alerts
|

Knock Down of Heat Shock Protein 27 (HspB1) Induces Degradation of Several Putative Client Proteins

Abstract: Hsp27 belongs to the heat shock protein family and displays chaperone properties in stress conditions by holding unfolded polypeptides, hence avoiding their inclination to aggregate. Hsp27 is often referenced as an anti-cancer therapeutic target, but apart from its well-described ability to interfere with different stresses and apoptotic processes, its role in non-stressed conditions is still not well defined. In the present study we report that three polypeptides (histone deacetylase HDAC6, transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 47 publications
1
88
0
1
Order By: Relevance
“…In contrast, downregulation of β-catenin seems not to affect Hsp27 levels, at least in the HepG2 hepatocellular carcinoma cell line (Wang et al 2011). We already mentioned that other molecules can be client proteins of Hsp27 (Gibert et al 2012). The roles of the N-and C-terminal sequences of Hsp27 on both, the chaperone activity of Hsp27 and in the self-association of this protein have recently been described (Lelj-Garolla and Mauk 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, downregulation of β-catenin seems not to affect Hsp27 levels, at least in the HepG2 hepatocellular carcinoma cell line (Wang et al 2011). We already mentioned that other molecules can be client proteins of Hsp27 (Gibert et al 2012). The roles of the N-and C-terminal sequences of Hsp27 on both, the chaperone activity of Hsp27 and in the self-association of this protein have recently been described (Lelj-Garolla and Mauk 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in human breast cancer tissues and in a rodent breast cancer cell line, Fanelli et al (2008) reported the interaction of β-catenin with Hsp27 and with HSF1, which may explain some of the molecular pathways that affect the prognosis of breast cancer patients. A recent study reported that histone deacetylase HDAC6, transcription factor STAT2 and procaspase-3 were degraded in human cancerous cells displaying genetically decreased levels of Hsp27 suggesting that they are client proteins of Hsp27 (Gibert et al 2012). The downregulation of Hsp27 in cancer cells caused senescence which has been associated with activation of the p53 pathway and induction of p21 (O'Callaghan-Sunol et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…HSP27 (encoded by HSPB1) is usually overexpressed in patients with breast cancer and affects the disease outcome and sensitivity of these patients to chemotherapy and radiotherapy (24,25). A recent study reported that histone deacetylase 6, transcription factor STAT2, and pro-caspase-3 were degraded in human cancer cells in which HSP27 was downregulated by siRNA transfection, suggesting that these are target proteins of HSP27 (21). A decrease in HSP27 expression by PDT may exert protective effects against PDT-induced cell death in oral cancer cells.…”
Section: Downregulation Of Hsp27 Affects Pdt-induced Cell Deathmentioning
confidence: 99%
“…We suggest that HSP70 expression is related to other proteins which regulate cell death and resistance in PDT. Regulation of HSP27 expression resulted in degradation of apoptotic protein and a delay in PDT-induced apoptosis by autophagy (21,22). Regulation of HSP27 expression may be one of the markers in PDT resistance and cancer therapy in oral cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent analysis of HSPB1 oligomerization/phosphorylation in cells exposed to different apoptotic inducers revealed that HSPB1 has multiple possibilities of forming different-sized and phosphorylated oligomers, suggesting that it can choose the more appropriate strategy to counteract apoptotic challenges triggered by unrelated inducers [30]. Another important feature is its ability to interact with a large number of client polypeptides, such as those we recently described: pro-caspase 3, histone deacetylase 6, and signal transducer and activator of transcription 2 [15]. Hence, in a particular cell condition, specific changes in oligomerization/ phosphorylation may allow HSPB1 to interact with the more appropriate polypeptides to allow cells to mount an adaptive response.…”
Section: Introductionmentioning
confidence: 96%